Multiple types of genomic variation contribute to adaptive traits in the mustelid subfamily Guloninae. Issue 10 (5th April 2022) - Derežanin, Lorena; Blažytė, Asta; Dobrynin, Pavel; Duchêne, David A.; Grau, José Horacio; Jeon, Sungwon; Kliver, Sergei; Koepfli, Klaus‐Peter; Meneghini, Dorina; Preick, Michaela; Tomarovsky, Andrey; Totikov, Azamat; et al.
Abstract: Species of the mustelid subfamily Guloninae inhabit diverse habitats on multiple continents, and occupy a variety of ecological niches. They differ in feeding ecologies, reproductive strategies and morphological adaptations. To identify candidate loci associated with adaptations to their respective environments, we generated a de novo assembly of the tayra ( Eira barbara ), the earliest diverging species in the subfamily, and compared this with the genomes available for the wolverine ( Gulo gulo ) and the sable ( Martes zibellina ). Our comparative genomic analyses included searching for signs of positive selection, examining changes in gene family sizes and searching for species‐specific structural variants. Among candidate loci associated with phenotypic traits, we observed many related to diet, body condition and reproduction. For example, for the tayra, which has an atypical gulonine reproductive strategy of aseasonal breeding, we observed species‐specific changes in many pregnancy‐related genes. For the wolverine, a circumpolar hypercarnivore that must cope with seasonal food scarcity, we observed many changes in genes associated with diet and body condition. All types of genomic variation examined (single nucleotide polymorphisms, gene family expansions, structural variants) contributed substantially to the identification of candidate loci. This argues strongly for consideration of variation other than single nucleotide polymorphisms in comparative genomics studies aiming to identify loci of adaptive significance.